Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbantuan Aplikasi Powtoon Terhadap Hasil Belajar Siswa Kelas - Fadlila Al Hasanah; Kartika Manalu; Sayed Akhyar (CAHAYA: Journal of Research on Science Education, 2025)
This research aims to determine the effect of learning using the Problem Based Learning model assisted by the Powtoon application on the learning outcomes of Class XI Madrasah Aliyah at the Islamic Education Park (TPI) Sawit Seberang. This research is a type of quantitative research with a Quasy Experimental Design. The research population was 36 students in class XI MIA A and 36 students in class XI MIA B, 36 students in class XI MIA C and 36 students in class, and X MIA C totaling 36 people as the control class. The instrument in this research is in the form of a test in the form of 30 multiple choice questions. Data analysis of student learning outcomes using the t-test formula, also with the help of SPSS version 25 data processing. Data analysis of student learning outcomes with the results of calculating the average learning outcomes shows that the experimental class which uses the Problem Based Learning models is higher than the control class. The prerequisite test is proven that the data is normally distributed and homogeneous. The results of the test calculation were obtained under count worth 9.709 and table worth 1.668 so that it shows tcount > table so Ha2 is accepted. The conclusions in this research explain that there are influences and differences before and after the implementation of the Problem Based Learning model on student learning outcomes in class XI Madrasah Aliyah at the Islamic Education Park (TPI) Sawit Seberang.